Kenya : Rural Electrification Access Expansion Study - de Gouvello, Christophe (World Bank, Washington, DC, 2013)
The Government of Kenya adopted in 2004 an Economic Recovery Strategy for Wealth and Employment Creation (ERSWEC), which recognizes three main pillars for economy recovery namely: (i) strengthening economic growth; (ii) enhancing equity and reducing poverty; and (iii) improving governance. The ERSWEC reiterates that the achievement of the three pillars is dependent on adequate and reliable access to least-cost energy. Since agriculture continues to be the mainstay of Kenya's economy, ensuring adequate access to electricity in rural areas is an important component to achieving the objectives of the ERSWEC. This is confirmed by investigations made by this study regarding specific energy needs for the different sectors of productive and social activities in the rural areas, for agriculture, livestock, fishery, tea and coffee cooperatives, telecommunications, water pumping and health and education services.The Government of Kenya has adopted a National Energy formulated in the Sessional Paper No 4 of 2004 consistent with the ERSWEC, which set double target of a 20% access rate to electricity in rural areas and 40% in 2020.